Human defensin 5 expression in intestinal metaplasia of the upper gastrointestinal tract. Issue 7 (23rd June 2005) - Shen, B; Porter, E M; Reynoso, E; Shen, C; Ghosh, D; Connor, J T; Drazba, J; Rho, H K; Gramlich, T L; Li, R; Ormsby, A H; Sy, M-S; et al.
Abstract : Background: Upper gastrointestinal tract intestinal metaplasia (IM) is termed Barrett's oesophagus (BO) or gastric intestinal metaplasia (GIM), depending on its location. BO and GIM are associated with chemical exposure resulting from gastro–oesophageal reflux and chronic Helicobacter pylori infection, respectively. Paneth cells (PCs), characterised by cytoplasmic eosinophilic granules, are found in a subset of IM at these sites, but histology may not accurately detect them. Aim: To determine human defensin 5 (HD5; an antimicrobial peptide produced by PCs) expression in BO and GIM, and to investigate its association with H pylori infection. Methods: Endoscopic biopsies from 33 patients with BO and 51 with GIM, and control tissues, were examined by routine histology and for H pylori infection and HD5 mRNA and protein expression. Results: In normal tissues, HD5 expression was specific for PCs in the small intestine. Five patients with BE and 42 with GIM expressed HD5, but few HD5 expressing cells in IM had the characteristic histological features of PCs. Most HD5 positive specimens were H pylori infected and most HD5 negative specimens were not infected. Conclusions: HD5 immunohistochemistry was often positive in IM when PCs were absent by conventional histology. Thus, HD5 immunohistochemistry may be superior to histology for identifying metaplastic PCs and distinguishing GIM from BO. The higher frequency of HD5 expression in GIM than in BO is associated with a higher frequency of H pylori infection, suggesting that in IM PCs may form part of the mucosal antibacterial response.